Studying the destruction of pollutant in the presence of photocatalysts based on MWCNTs with controlled values of TiO2 nanoparticles - Sedigheh Abbasi (Applied Water Science, 2023)
Abstract The main goal of the present research is the synthesis of new photocatalysts to reduce the amount of organic pollutants in aquatic environments. For this purpose, the amount of TiO2 nanoparticles in the synthesized samples containing MWCNTs is controlled to synthesize two types of photocatalysts named as MCT#1 and MCT#2. Samples characterizing using XRD reveal that the TiO2 nanoparticles have a combined phase of rutile and anatase. So that in both of photocatalysts, the percentage of anatase phase is higher than rutile. The analysis of the degradation rate demonstrates that intensification level of TiO2 nanoparticles in MCT#2 compared to the MCT#1 leads to enhancement of photocatalytic activity of MCT#2. Design of experiment results shows that the destruction amount of MO is affected by irradiation time and pH. Based on ANOVA study, it is observed that both factors have a significant effect on reducing of MO concentration. Analyzing the results based on Duncan's multiple range test at α = 0.05 confirm that all the studied levels of the main parameters have a logical influence on MO destruction. Meanwhile, it can be deducted that the most and the least of destruction is observed at pH = 7 and pH = 3, respectively.